Descrição do genoma, transcriptoma e microbioma de Stenostomum leucops (Platyhelminthes, Catenulida), com enfoque na filogenia, regeneração, plasticidade ecológica e elementos transponíveis. - Rosa, Marcos Trindade da (2022)
Platyhelminthes is the phylum with the highest adaptive radiation of invertebrates, and is currently divided into five classes: Catenulide, Rhabditophora, Monogenea, Cestoda and Trematoda. Phylogenetic analyses, using 12 mitochondrial genes from 165 species of Platyhelminthes, position Catenulide as a sister group to Rhabditophora. Long read sequencing revealed, in some Platyhelminthes species, that mitogenomes can be larger than those presented by short read sequencing. S. leucops has few differentiated tissues and is rich in stem cells, responsible for its regeneration and reproduction. The literature presents contradictory descriptions about regenerative aspects of S. leucops in the zooid formation, when the anterior cephalic part and the posterior body are removed. The experiments redone by us, found that all the regeneration ways described in the literature, can be obtained. The microbiome of S. leucops seems to go beyond simple food for the worm, as it has the capacity to express DNA contained in bacteria (plasmid with gfp marker). S. leucops is also able to utilize “free DNA” present in its environment, even at lower rates, when compared to that available in the microbiome. We analyzed the microbiome of S. leucops in an isolineage maintained for 12 years in laboratory culture, and variations in its cultivation caused by the pandemic (home cultivation) and collection from nature today. The microbiome of S. leucops is not rigid, as in the case of another Catenulide that has a well-studied microbiome, Paracatenula sp. This doctoral thesis also brings DNA and RNA sequencing, in addition to previous data from their respective assemblies and annotations. The sequences come from the Illumina, Oxford Nanopore and IonTorrent S5 methodologies.